Eksistensi Digital Wedding Di Era Disrupsi Dalam Maqashid Syariah - SALWA NAILA; AHMAD ZAID; FATIMAH HUSNA AZZAHRA; RAHMAT FADILLAH (PT. Sharia Journal and Education Center, 2024)
Abstract The era of disruption has presented a new phenomenon in wedding procedures, namely digital weddings. The emergence of digital marriage raises questions about its validity in Islam and how digital marriage can fulfill the maqashid of sharia. An in-depth analysis of digital marriage in the context of maqashid sharia is needed to answer these questions. Important points that need to be considered include the pillars and conditions of marriage, the presence of a marriage guardian, security and privacy, compliance with maqashid sharia, as well as challenges and solutions. Digital marriage must fulfill the pillars and requirements of marriage, and be able to fulfill the maqashid of sharia. The security and privacy of personal data of the parties involved also needs to be considered. Digital marriage still has several challenges that need to be overcome, such as ensuring the validity of the marriage, ease of access for all groups, and public education. This research uses normative research methods and a conceptual analysis approach to analyze the existence of digital weddings in the era of technological disruption by taking into account the maqashid sharia perspective. Data was collected from related literature and analyzed to examine the main elements of the concept of digital marriage, technology, maqashid sharia, and the era of disruption. The author also considers the application of maqashid sharia principles to the development and implementation of digital marriage based on basic principles such as justice, benefit and blessing. This research provides an understanding of the development of digital marriage in the era of digital technology and its application to social, economic and cultural aspects. Discussions about digital marriage are still ongoing and there is no unified opinion among the ulama about its validity. Digital marriages need to be carried out by paying attention to local norms and customs, and the public needs to receive sufficient education about digital marriages so they can understand their rights and obligations. Keywords: existence; digital wedding; era of disruption;, maqashid sharia. Abstrak Era disrupsi menghadirkan fenomena baru dalam tata cara pernikahan, yaitu pernikahan digital. Kemunculan pernikahan digital menimbulkan pertanyaan tentang keabsahannya dalam Islam dan bagaimana pernikahan digital dapat memenuhi maqashid syariah. Analisis mendalam terhadap pernikahan digital dalam konteks maqashid syariah diperlukan untuk menjawab pertanyaan-pertanyaan tersebut. Poin penting yang perlu dipertimbangkan meliputi rukun dan syarat pernikahan, kehadiran wali nikah, keamanan dan privasi, pemenuhan maqashid syariah, serta tantangan dan solusinya. Pernikahan digital harus memenuhi rukun dan syarat pernikahan, serta mampu memenuhi maqashid syariah. Keamanan dan privasi data pribadi para pihak yang terlibat pun perlu diperhatikan. Pernikahan digital masih memiliki beberapa tantangan yang perlu diatasi, seperti memastikan keabsahan pernikahan, kemudahan akses bagi semua kalangan, dan edukasi masyarakat. Penelitian ini menggunakan metode penelitian normatif dan pendekatan analisis konseptual untuk menganalisis eksistensi digital wedding dalam era disrupsi teknologi dengan memperhatikan perspektif maqashid syariah. Data dikumpulkan dari literatur-literatur terkait dan dianalisis untuk mengkaji elemen utama dari konsep digital wedding, teknologi, maqashid syariah, dan era disrupsi. Penulis juga mempertimbangkan implikasi prinsip-prinsip maqashid syariah pada pengembangan dan implementasi digital wedding berdasarkan prinsip dasar seperti keadilan, kemaslahatan, dan keberkahan. Penelitian ini memberikan pemahaman tentang perkembangan digital wedding di era teknologi digital dan implikasinya pada aspek sosial, ekonomi, dan budaya. Pembahasan tentang pernikahan digital masih berlangsung dan belum ada kesatuan pendapat di kalangan ulama tentang keabsahannya. Pernikahan digital perlu dilakukan dengan memperhatikan norma dan adat istiadat setempat, serta masyarakat perlu mendapatkan edukasi yang cukup tentang pernikahan digital agar dapat memahami hak dan kewajiban mereka. Kata Kunci: eksistensi; digital wedding; era disrupsi; maqashid syariah.